Molecular Identification and Novel Mitochondrial COI Gene Haplotypes of Nesting Kemp’s Ridley Turtles (Lepidochelys kempii) in Rancho Nuevo Sanctuary, Mexico - Fátima Yedith Camacho-Sánchez; José Alberto Narváez-Zapata; Héctor Hugo Acosta-Sánchez; Martha López-Hernández; Agusto Luzariaga-Neira; Hervey Rodríguez-González; A. Alonso Aguirre; Miguel Angel Reyes-López (Diversity, 2022)
One hundred new COI sequences of nesting female Kemp’s ridley turtles (Lepidochelys kempii) were obtained in the Rancho Nuevo Sanctuary (RNS). The COI sequences were analyzed and contrasted with others retrieved from BOLD and GenBank with the aim of investigating genetic variability, genetic divergence, and haplotypes of the nesting female population at RNS. Four new COI haplotypes for Kemp’s ridley were described; two are redundant with (LK-RN01) 97 and (LK-COI-01) 17 specimens belonging to the RNS and other localities, respectively. Nucleotide (0.00052) and haplotype (0.303) diversity showed low and conserved COI values The fixation index (FST) between these main redundant haplotypes showed a high degree of differentiation with ~1. Genetic divergence clearly demonstrated two different Kemp’s ridley nesting populations, one from RNS and a second outside Mexico. Phylogenetic COI analysis was useful to differentiate these redundant (LK-COI-01 and RNS LK-RN01) haplotypes and, therefore, these different Kemp’s ridley populations. In addition, phylogenetic COI analysis clearly separates Kemp’s ridley turtles from other sea turtle species, supporting its use as a barcode marker.